Therapeutic effects of LASSBio-596 in an elastase-induced mouse model of emphysema - Padilha, Gisele A.; Henriques, Isabela; Lopes-Pacheco, Miquéias; Abreu, Soraia C.; Oliveira, Milena V.; Morales, Marcelo M.; Lima, Lidia M.; Barreiro, Eliezer J.; Silva, Pedro L.; Xisto, Debora G.; Rocco, Patricia R. M. (Frontiers in Physiology, 2015)
Emphysema is an intractable pulmonary disease characterized by an inflammatory process of the airways and lung parenchyma and ongoing remodeling process in an attempt to restore lung structure. There is no effective drug therapy that regenerates lung tissue or prevents the progression of emphysema; current treatment is aimed at symptomatic relief. We hypothesized that LASSBio-596, a molecule with potent anti-inflammatory and immunomodulatory effects, might reduce pulmonary inflammation and remodeling and thus improve lung function in experimental emphysema. Emphysema was induced in BALB/c mice by intratracheal administration of porcine pancreatic elastase (0.1 IU) once weekly during 4 weeks. A control group received saline using the same protocol. After the last instillation of saline or elastase, dimethyl sulfoxide or LASSBio-596 were administered intraperitoneally, once daily for 8 days. After 24 h, in elastase-induced emphysema animals, LASSBio-596 yielded: 1) decreased mean linear intercept, hyperinflation and collagen fiber content, 2) increased elastic fiber content, 3) reduced number of M1 macrophages, 4) decreased tumor necrosis factor-α, interleukin-1β, interleukin-6, and transforming growth factor-beta protein levels in lung tissue, and increased vascular endothelial growth factor. These changes resulted in increased static lung elastance. In conclusion, LASSBio-596 therapy reduced lung inflammation, airspace enlargement, and small airway wall remodeling, thus improving lung function, in this animal model of elastase-induced emphysema.